Vakuumska molekularna destilacija - Povh, Bojan (Vakuumist, 1999)
In the paper the principle and design of laboratory and industrial plants for the distillation of high-boiling and heat-sensitive compounds in the fine and high vacuum range are explained. The distillation in the vacuum range requres not only appropriate vacuum pumps but also special apparatus and machines. Different destillation procedures are explained and various types of appartus are described. The advantages of vacuum molecular distillation are also found and various fields of applocation are described.
Keywords: termodifuzijske operacije; vakuumska destilacija; molekularna destilacija